A simple and general strategy for postsurgical personalized cancer vaccine therapy based on an injectable dynamic covalent hydrogel. (10th September 2021) - Yu, Zhentao; Xu, Yudi; Yao, Haochen; Si, Xinghui; Ji, Guofeng; Dong, Si; Zhao, Jiayu; Tang, Zhaohui; Fang, Xuedong; Song, Wantong; Chen, Xuesi
Abstract : A dynamic covalent hydrogel-based vaccine (DCHVax) for personalized postsurgical therapy of tumors was developed. Tumor lysates were extracted; then DCHVax was prepared and injected back to the host for eliciting tumor-specific immune responses. Abstract : Cancer vaccines artificially stimulate the immune system against cancer and are considered the most promising treatment of cancer. However, the current progress in vaccine research against cancer is still limited and slow, partially due to the difficulties in identifying and obtaining tumor-specific antigens. Considering surgery as the first choice for tumor treatment in most cases, the authors evaluated whether the resected tumor can be directly used as a source of tumor antigens for designing personalized cancer vaccines. Based on this idea, herein, the authors report a dynamic covalent hydrogel-based vaccine (DCHVax) for personalized postsurgical management of tumors. The study uses proteins extracted from the resected tumor as antigens, CpG as the adjuvant, and a multi-armed poly(ethylene glycol) (8-arm PEG)/oxidized dextran (ODEX) dynamically cross-linked hydrogel as the matrix. Subcutaneous injection of DCHVax recruits dendritic cells to the matrix in situ and elicits robust tumor-specific immune responses. Thus, it effectively inhibits the postoperative growth of the residual tumor in several murine tumor models. This simple and personalized method to develop cancer vaccines may be promising in developing clinically relevant strategies for postoperative cancer treatment.